Patient satisfaction and medication adherence assessment in diabetes medication therapy adherence clinic (MTAC) / Zanariah Abu Bakar - Abu Bakar, Zanariah (2015)
The measurement of patient satisfaction and adherence are indeed important in disease management services especially in chronic disease as a mean of service benefit and quality assurance. This study aims to determine the satisfaction and adherence of diabetes mellitus patients at the DMTAC and to determine the relationship between patient satisfaction and adherence. The questionnaires were guided administered by the researcher and consists of three sections. 1) Socio-demographic, medical and medication history and clinical parameters, 2) Patient Satisfaction with Pharmaceutical Care Questionnaire (PSPCQ) and 3) The eight-item Morisky Medication Adherence Scale (MMAS). 165 patients from Hospital Sultanah Aminah, Hospital Sultanah Nora Ismail and Hospital Pakar Sultanah Fatimah who had received counselling at DMTAC were recruited. Data were analysed with SPSS 18.0, using the descriptive statistics and non-parametric tests. The majority were female (50.9%), aged > 60 years (40.0%), Malay (72.7%), had secondary education level (55.2%) and were unemployed (56.4%). Most of the patients had at least 4 visits (60.6%), had diabetes for more than 5 years (80.0%), on both oral and insulin (55.2%) and had 2 comorbidities (43.0%). 87% of patients were satisfied with DMTAC service (score 60-100) with mean scores of 76.8 and 26.1% had high adherence (score=8). There was a significant (p<0.01), positive fair correlation (rs=0.377) between satisfaction and adherence. This study leads to better understanding on which area of satisfaction and adherence needs to be emphasized on patients at DMTAC. Such information was important in designing interventions to enhance patient satisfaction and adherence.